Analisis Kualitas Layanan Sports Massage di Kota Surabaya dengan Menggunakan Pendekatan SERVQUAL - Mulyono; Eka Kurnia Darisman; Gatot Margisal Utomo (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The development of sports massage services in large cities such as Surabaya requires service providers to deliver service quality that meets customer expectations. This study aimed to analyze the service quality of sports massage services in Surabaya using the SERVQUAL approach. A descriptive quantitative method with a survey design was employed. The research sample consisted of 100 respondents who were users of sports massage services, selected using an accidental sampling technique. The research instrument was a SERVQUAL questionnaire comprising five dimensions: tangibles, reliability, responsiveness, assurance, and empathy, measured using a 5-point Likert scale. Data were analyzed descriptively by calculating the mean scores of perceptions, expectations, and the service quality gap (perception–expectation). The results indicated that all SERVQUAL dimensions exhibited negative gap values, suggesting that customers’ perceptions had not fully met their expectations. The largest gaps were found in the reliability and assurance dimensions (–0.57), while the smallest gap was observed in the responsiveness dimension (–0.52). In conclusion, the quality of sports massage services in Surabaya can be categorized as good; however, improvements are still required, particularly in service reliability and assurance, to optimally meet customer expectations.